Spatio-temporal distribution of subsidy on major livestock inputs and services in India - Priyanka Lal; B S Chandel (Agricultural Economics Research Review, 2023)
We estimate the subsidies on the major inputs and services to the livestock sector in India. The livestock subsidy increased at 7% per annum from 2006 to 2017. Of the total livestock subsidy, veterinary and health services accounted for 75%, and livestock insurance the least, although it grew at a high rate. We also construct an agricultural development index. The rank correlation between the livestock subsidy and the index shows that the allocation of subsidy is higher to states that rank low on the index, as it should be, because less developed regions need more support for growth and development.